The main indicators for iranian hospital ethical accreditation - SEYED ALI ENJOO; MITRA AMINI; SEYED ZIAADIN TABEI; ALI MAHBUDI; ZAHRA KAVOSI; MAHBOOBEH SABER (Journal of Advances in Medical Education and Professionalism, 2015)
Introduction: The application of organizational ethics in hospitals is one of the novel ways to improve medical ethics. Nowadays achieving efficient and sufficient ethical hospital indicators seems to be inevitable. In this connection, the present study aims to determine the best indicators in hospital accreditation. Methods: 69 indicators in 11 fields to evaluate hospital ethics were achieved through a five-step qualitative and quantitative study including literature review, expert focus group, Likert scale survey, 3 rounded Delphi, and content validity measurement. Expert focus group meeting was conducted, employing Nominal Group Technique (NGT). After running NGT, a three rounded Delphi and parallel to Delphi and a Likert scale survey were performed to obtain objective indicators for each domain. The experts were all healthcare professionals who were also medical ethics researchers, teachers, or Ph.D students. Content validity measurements were computed, using the viewpoints of two different expert groups, some ethicists, and some health care professionals (n=46). Results: After conducting NGT, Delphi, Likert survey, 11 main domains were listed including: Informed consent, Medical confidentiality, Physician-patient economic relations, Ethics consultation policy in the hospital, Ethical charter of hospital, Breaking bad medical news protocol, Respect for the patients’ rights, Clinical ethics committee, Spiritual and palliative care unit programs in the hospitals, Healthcare professionals’ communication skills, and Equitable access to the healthcare. Also 71 objective indicators for these 11 domains were listed in 11 tables with 5 to 8 indicators per table. Content Validity Ratio (CVR) measurements were done and 69 indicators were highlighted. Conclusion: The domains listed in this study seem to be the most important ones for evaluating hospital ethics programs and services. Healthcare organizations’ accreditation and ranking are crucial for the improvement of healthcare services. Ethics programs would also motivate hospitals to improve their services and move towards patients’ satisfaction. In this regard, more involvement of bioethicists can help healthcare organizations to develop ethics programs and ensure ethicsbased practice in hospitals.